PENDIDIKAN ANAK USIA DINI (PAUD) PERSPEKTIF PENDIDIKAN ISLAM - Imron, Imron (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2009)
Having children is part of the exam given to our God (Sura Al-Anfal verse 28). Therefore the child entrusted to Allah Almighty that we must protect and nurture our students so that humans help and continues to radiate the glory of his personality. The task of parents and teachers in schools within the framework of education for children is to help children discover and empower potential. This is done since an early age children are still (since childhood) until the children find themselves and become adults. Therefore the Government, early childhood education is done in two dimensions, namely (1) Early Childhood Education in Family and (2) early childhood education in formal education. Looking at the above two dimensions, so that parents and teachers plays a fundamental role in developing a child's potential. This is where the seriousness required of parents and teachers are good to get maximum results.